2022
DOI: 10.1037/rel0000300
|View full text |Cite
|
Sign up to set email alerts
|

Religiosity and positive religious coping as predictors of Indonesian Muslim adolescents’ externalizing behavior and loneliness.

Abstract: Loneliness and antisocial behavior were predicted from religiosity and positive religious coping in this 1-year longitudinal study of 564 16-year-old Indonesian Muslim adolescents. An externalizing behavior construct was formed from 3 variables (i.e., self-reported tobacco and alcohol use, self-reported problem behavior, and peer-rated aggression). Loneliness was self-reported. Externalizing behavior was significantly predicted by religiosity in concurrent analyses and marginally predicted by religiosity in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 53 publications
0
24
0
Order By: Relevance
“…The findings of meta-analysis underscore the vital role of religious coping in psychological adjustment to stress (Ano and Vasconcelles 2005 ). Previous studies have demonstrated that positive religious coping is positively related to psychological well-being (Lewis et al 2005 ), psychological, physical, and spiritual adjustments (Pargament et al 2004 ), and externalizing behaviours (French et al 2020 ). Negative religious coping was found to be related to poor quality of life such as worse physical functioning, role physical, vitality, social functioning, and mental health over and above the sociodemographic, clinical, and anxiety and depression factors (Taheri-Kharameh et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of meta-analysis underscore the vital role of religious coping in psychological adjustment to stress (Ano and Vasconcelles 2005 ). Previous studies have demonstrated that positive religious coping is positively related to psychological well-being (Lewis et al 2005 ), psychological, physical, and spiritual adjustments (Pargament et al 2004 ), and externalizing behaviours (French et al 2020 ). Negative religious coping was found to be related to poor quality of life such as worse physical functioning, role physical, vitality, social functioning, and mental health over and above the sociodemographic, clinical, and anxiety and depression factors (Taheri-Kharameh et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, higher use of religious and spiritual beliefs during the COVID-19 pandemic was related to better mental health outcomes including hope and spiritual growth (Lucchetti et al 2020 ). There is also a close link between religious coping strategies and loneliness, for example, in a recent study, positive religious coping was found to be negatively associated with loneliness both concurrently and longitudinally (French et al 2020 ). Another study reported significant effects of religious coping on loneliness and depression (Warner et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our study identified two factors that may benefit student mental health during the pandemic. Strong family relationships and religiosity are two social and cultural features of Indonesian university students that also reflect those of the wider Indonesian society (French et al, 2020;Purwono et al, 2019). We hypothesised that these two key characteristics might help to mitigate mental health issues among university students during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Strong family relationships and religiosity are two social and cultural characteristics of Indonesian university students, which are also reflected in Indonesian society at large (French et al, 2020;Purwono et al, 2019). Indonesians are very family-oriented, meaning that family relationships are very close, and characterised by mutual love and an obligation to take care of each other.…”
Section: Contextsmentioning
confidence: 99%
“…We chose Indonesia as the location for our research as religious belief is fairly high amongst its population (French et al , 2020). Many Indonesians’ organisational values and cultures adopt and adapt to beliefs and religion (French et al , 2008; Purwono et al , 2019).…”
Section: Introductionmentioning
confidence: 99%